Financial Distress: Corporate Governance Structure dan Financial Indicator pada Perusahaan Manufaktur di Indonesia - Fahik, Yohanes; Safriliana, Retna (Jurnal Bisnis dan Manajemen, 2022)
The purpose of this study was to examine the variables causing financial distress, namely the corporate governance structure and financial indicators. Corporate governance (corporate governance structure) is measured by managerial ownership and institutional ownership. While financial indicators are measured by liquidity, profitability and leverage. All manufacturing businesses that are listed and have published their financial statements between 2019 until 2021 are the population of this study. Based on the purposive sampling used, the sample of this study amounted to obtain 48 data. Multiple linear regression is a data analysis method used to test the data. The findings of this study indicate that the condition of financial distress or financial difficulty is influenced by financial indicators represented by profitability and leverage. The state of financial distress is not influenced by corporate governance as measured by management ownership, institutional ownership, and financial indicators as measured by liquidity.